Cell-trafficking impairment in disease-associated LPA6 missense mutants and a potential pharmacoperone therapy for autosomal recessive woolly hair/hypotrichosis. Issue 5 (29th September 2022) - Yanagida, Keisuke; Masago, Kayo; Yasuda, Daisuke; Hamano, Fumie; Kurikawa, Yoshitaka; Shimizu, Takao; Ishii, Satoshi
Abstract: In human autosomal recessive woolly hair/hypotrichosis (ARWH/HT), many mutations have been identified in a gene encoding LPA6, a G protein-coupled receptor (GPCR) for lysophosphatidic acid (LPA). However, information regarding the effects of such mutations on receptor function is limited. In this study, we examined functional impacts of selected amino acid changes in LPA6 identified in ARWH/HT patients. In our exogenous expression experiments, all mutants except S3T failed to respond to LPA, indicating that they are loss-of-function mutants. Among the nine mutants, five (D63V, G146R, N246D, L277P and C278Y) displayed impaired expression at the cell surface because of endoplasmic reticulum (ER) retention, indicating that these mutants are trafficking-defective, as reported in other disease-associated GPCRs. Notably, alkyl-OMPT, a potent synthetic agonist for LPA6 restored the defective cell surface expression of two of the ER-retained mutants, D63V and N246D, possibly by its chaperoning function that allows them to escape intracellular retention as well as proteasomal degradation. Furthermore, the alkyl-OMPT-rescued N246D mutant was shown be functional. Our findings encourage future application of pharmacoperone therapy for ARWH/HT patients with specific LPA6 mutations.